Survival of the Fittest: The Relationship of (p)ppGpp With Bacterial Virulence - Kundra, Shivani; Colomer-Winter, Cristina; Lemos, José A. (Frontiers in Microbiology, 2020)
The signaling nucleotide (p)ppGpp has been the subject of intense research in the past two decades. Initially discovered as the effector molecule of the stringent response, a bacterial stress response that reprograms cell physiology during amino acid starvation, follow-up studies indicated that many effects of (p)ppGpp on cell physiology occur at levels that are lower than those needed to fully activate the stringent response, and that the repertoire of enzymes involved in (p)ppGpp metabolism is more diverse than initially thought. Of particular interest, (p)ppGpp regulation has been consistently linked to bacterial persistence and virulence, such that the scientific pursuit to discover molecules that interfere with (p)ppGpp signaling as a way to develop new antimicrobials has grown substantially in recent years. Here, we highlight contemporary studies that have further supported the intimate relationship of (p)ppGpp with bacterial virulence and studies that provided new insights into the different mechanisms by which (p)ppGpp modulates bacterial virulence.